Ritual Adat Rsaw Lasmyer/Tikam Tanah Di Desa Namtabung Kecamatan Selaru Kabupaten Kepulauan Tanimbar - Nureroan, Melki A; Hetharion, Bety D.S.; Far-Far, Gazali (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2022)
The Rsaw Lasmyer ritual in Namtabung is mandatory for newcomers entering the village of Namtabung. Rsaw Lasmyer holds a unique appeal and carries significant value for those new to the town. This research aims to understand the process of the Rsaw Lasmyer ritual and the values it holds for the people of Namtabung. The study employs qualitative research using an ethnographic approach, which involves a description of a culture through an anthropological lens. The findings indicate that the Rsaw Lasmyer ritual in Namtabung is a form of traditional tikam tanah where both newcomers and locals who have never entered the village must undergo the ritual. The Rsaw Lasmyer ritual consists of four stages. Before the ritual begins, newcomers must place sand on their foreheads and walk to the front of the village to start the Rsaw Lasmyer process, visiting each house of the village chief (Raja). The ritual involves the use of specific tools to offer food and drink to the ancestors, with family members accompanying the newcomer throughout the process. Changes in the Rsaw Lasmyer ritual have occurred, particularly in the attributes and trays (nyiru) used. The values embodied in the ritual signify that newcomers cannot be disturbed, as they are now considered part of the Namtabung community.